If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -1z) = 5 Remove parenthesis around (3 + -1z) 3 + -1z = 5 Solving 3 + -1z = 5 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1z = 5 + -3 Combine like terms: 3 + -3 = 0 0 + -1z = 5 + -3 -1z = 5 + -3 Combine like terms: 5 + -3 = 2 -1z = 2 Divide each side by '-1'. z = -2 Simplifying z = -2
| -13x+8+8x=-9x-22 | | h=-16t^2-17t+120 | | z^2+8z-20= | | 6x^5+35x^4+36x^3-79x^2-96x+18=0 | | -.20x+1=-7 | | 4(4+5x)=216 | | 21.54=30+18x | | 2x+10-(7x-(12(x-1)-5))=5(x-3) | | 7p-(3p+4)=-2p-1+10 | | 30+18x=21.54 | | 20x^3+100x^2=0 | | 34x-16+15x^2=0 | | 9x+10=-2(x+3)+3x | | r^4=3r^3+18r^2 | | 10x+8=65+13x | | y^2=x+1 | | 12=-14B+3B | | 0.14-0.01(x-2)=-0.02(3-x) | | X-x(3x-5)=x-2(x(x)+x)-x(x)-14 | | S=2(3.14)rh+(3.14) | | y=14-2y | | -6-3=9r-6 | | 0.10(x+10)+0.70x=17 | | 4(2x-5)=3x+13 | | 10P+8=5P-2 | | 13-22=-3x | | 16-3b=0 | | 5=7Y-5Y-3 | | y^2+13y+12= | | 16-36=0 | | 10B-11B=0 | | 2(-4+p)=-8.2+1.8p |